2019
DOI: 10.3390/su11195193
|View full text |Cite
|
Sign up to set email alerts
|

Learning and Parenting in Spanish Environments: Prosocial Behavior, Aggression, and Self-Concept

Abstract: The psychology of sustainability and sustainable development is related to improvements in people’s quality of life in different environments, including the family. Based on this theoretical approach, this study explores the relationships between parenting styles (maternal and paternal support, control, and neglect) and prosocial behavior, aggression, and self-concept of children from Spain aged 4–7 years (M = 5.81; DS = 1.05). Participants were 635 boys and girls (53.7% boys; 46.3% girls) from Valencia and Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 63 publications
0
22
0
5
Order By: Relevance
“…First, we should pay careful attention to the parental upbringing styles when attempting to prevent episodes of loneliness. As suggested by previous research, parenting styles have substantial effects on the general self-concept as well as behavioural outcomes (Bagán et al, 2019;Chen et al, 2020). Parents should thus reduce the use of negative educational methods in order to meet the emotional needs of their children within the family context while also paying more attention to their formative processes and levels of loneliness.…”
Section: Limitations and Suggestionsmentioning
confidence: 89%
See 2 more Smart Citations
“…First, we should pay careful attention to the parental upbringing styles when attempting to prevent episodes of loneliness. As suggested by previous research, parenting styles have substantial effects on the general self-concept as well as behavioural outcomes (Bagán et al, 2019;Chen et al, 2020). Parents should thus reduce the use of negative educational methods in order to meet the emotional needs of their children within the family context while also paying more attention to their formative processes and levels of loneliness.…”
Section: Limitations and Suggestionsmentioning
confidence: 89%
“…This result is congruent with previous findings regarding the influence of parental upbringing styles on both the general self-concept. For example, research shows that if parents adopt positive parenting methods, such as parental support, it will help teenagers to form positive development results, such as prosocial behavior and self-concept development ( Bagán et al, 2019 ). However, negative parenting styles in which adolescents experience parental punishment, parental rejection, and low parental emotional warmth lead to negative developmental outcomes for adolescents, including increased aggressive behaviour and a negative general self-concept ( Wu et al, 2015 ; Zubizarreta et al, 2019 ; Luo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of the parental motivational orientations in the development of the children's corresponding orientations and well-being suggests that changing academic adaptation might be possible by operating early interventions at the parents' level. Further research is necessary to explore why performance-approach goals had a positive impact on well-being in this cultural context, as previous studies revealed that this type of goal orientation may be detrimental to well-being.Sustainability 2020, 12, 1785 2 of 24 development of children and adolescents (e.g., [6][7][8][9][10][11]). On the basis of the existing parenting models in the literature, three characteristics of parents influencing the development of children were identified: the parents' beliefs (values and goals in socializing their children); the parenting practices they employ; and the parenting style as a more global configuration of different parenting practices reflecting the parents ' beliefs, attitudes, or values [12].…”
mentioning
confidence: 99%
“…Sustainability 2020, 12, 1785 2 of 24 development of children and adolescents (e.g., [6][7][8][9][10][11]). On the basis of the existing parenting models in the literature, three characteristics of parents influencing the development of children were identified: the parents' beliefs (values and goals in socializing their children); the parenting practices they employ; and the parenting style as a more global configuration of different parenting practices reflecting the parents ' beliefs, attitudes, or values [12].…”
mentioning
confidence: 99%